A Review of Obstructive Sleep Apnea Treatment: The Role of Surgery in Therapy and Alternative Treatment Modalities - Zielonka, Kacper; Jasińska, Joanna; Dądela, Bartosz; Markowski, Marcin; Śliwa, Natalia; Majewska, Emilia Maria; Kawalska, Eliza; Gnitecki, Szymon; Janczura, Szymon; Borowski, Maciej (Quality in Sport, 2025)
Obstructive sleep apnea (OSA) is a common sleep disorder involving repeated upper airway obstructions during sleep, leading to hypoxia, fragmented sleep, and excessive daytime sleepiness. It is linked to significant cardiovascular and metabolic risks and affects 17-30% of individuals aged 30-69, with higher rates in the elderly. Diagnosis is typically made using polysomnography, which assesses the frequency and severity of apneic events. Treatment mainly involves continuous positive airway pressure (CPAP), although adherence can be challenging. Alternative therapies like oral appliances, positional therapy, and lifestyle modifications are helpful for milder cases. Medications such as GLP-1 receptor agonists, acetazolamide and 5-HT regulating have shown promise in reducing symptoms and improving CPAP compliance. Surgical options, such as uvulopalatopharyngoplasty (UPPP), maxillomandibular advancement (MMA), transoral robotic surgery (TORS) and tracheostomy, are considered when other treatments fail, particularly in patients with anatomical issues. Bariatric surgery can also reduce OSA severity in severely obese patients. Emerging therapies like hypoglossal nerve stimulation (HGNS), orofacial myofunctional therapy (OMT), and cognitive behavioral therapy for insomnia (CBT-I) offer solutions for patients who cannot tolerate CPAP. Advancements in AI and telemedicine are improving diagnosis and treatment personalization. OSA treatment requires a tailored approach, considering individual factors and comorbidities. Continued research is essential to optimize long-term care.